2021
DOI: 10.1055/s-0041-1734356
|View full text |Cite
|
Sign up to set email alerts
|

Facial Nerve Schwannoma: The Rare/Great Mimicker of Vestibular Schwannoma/Neuroma

Abstract: Schwannomas are benign tumors arising from Schwann cells which are a protective casing of nerves, composing myelin sheath and can develop in any nerve where Schwann cells are present. Most common are vestibulocochlear nerve schwannomas. Facial nerve schwannomas (FNSs) are uncommon tumors involving seventh nerve of which geniculate ganglion involvement is most common. Clinical presentations and the imaging appearances of FNSs are influenced by the topographical anatomy of the facial nerve and vary according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…FNS is rare, accounting for less than 1% of all temporal bone tumors [ 9 ]. It originates from the Schwann cell, confines within a capsule and stays at the periphery of the facial nerve.…”
Section: Discussionmentioning
confidence: 99%
“…FNS is rare, accounting for less than 1% of all temporal bone tumors [ 9 ]. It originates from the Schwann cell, confines within a capsule and stays at the periphery of the facial nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Facial nerve schwannomas were differentiated from vestibular nerve schwannomas by intraoperative findings or by neurological features and radiologic characteristics. 1,3 Facial nerve schwannoma patients had more facial nerve function deficits along with tumor involvement of the temporal bone or extra temporal segments. 3 All imaging was reviewed by experienced neuroradiologists, as well as radiosurgical teams practicing at tertiary or quaternary referral centers.…”
Section: Patient Populationmentioning
confidence: 99%
“…1,3 Facial nerve schwannoma patients had more facial nerve function deficits along with tumor involvement of the temporal bone or extratemporal segments. 3 All imaging was reviewed by experienced neuroradiologists, as well as radiosurgical teams practicing at tertiary or quaternary referral centers. If there is any doubt about the diagnosis of a facial schwannoma, the patient was excluded from the study.…”
Section: Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Although NFN were mostly managed by surgical resection, the timing of surgery is controversial due to the inevitability of post-operative House-Brackman grade III facial palsy. [3][4][5] It has been demonstrated that fractionated stereotactic radiotherapy (FSRT) has been effective for acoustic neuromas of the cerebellopontine angle or internal auditory canal with minimal morbidity. 6 Our purpose is to systematically review the literature about FSRT on the treatment of NFN.…”
Section: Introductionmentioning
confidence: 99%